FEASIBILITY ANALYSIS OF FISH FLOUR BUSINESS IN KEMBANG DAHLIA SMEs, BUKI DISTRICT, SELAYAR ISLANDS REGENCY - Rahmi Sari; Mutemainna Karim; Awaluddin Awaluddin; Muh. Ayusal Salam (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi dan Bisnis Maritim Balik Diwa, 2026)
The fish processing industry plays an important role in increasing the added value of fisheries products and strengthening the economic resilience of coastal communities. This study aimed to evaluate the financial feasibility of the fish floss business operated by Kembang Dahlia SME in Buki District, Selayar Islands Regency. The research was conducted from May to July 2025 using a case study approach. Primary data were collected through observations, interviews, documentation, and structured questionnaires, while secondary data were obtained from institutional reports and relevant literature. Financial feasibility was analyzed using investment cost analysis, production cost analysis, Break-Even Point (BEP), Net Present Value (NPV), Benefit-Cost Ratio (BCR), and Internal Rate of Return (IRR). The results showed that the enterprise required an initial investment of IDR 25,170,000 and maintained annual production costs ranging from IDR 43.13 million to IDR 47.60 million during 2022–2024. Annual revenues ranged from IDR 109.50 million to IDR 136.05 million, generating net profits between IDR 66.37 million and IDR 88.45 million. The business consistently produced above the break-even production level, while the selling price remained substantially higher than the break-even price. Financial feasibility indicators demonstrated positive results, including an NPV of IDR 53,648,180, a BCR of 1.35, and an IRR of 123%, all exceeding the accepted investment criteria. These findings indicate that the fish floss business operated by Kembang Dahlia SME is financially feasible, profitable, and sustainable. Strengthening production capacity, improving product diversification, and expanding market access are recommended to enhance long-term business competitiveness and profitability